PUBLIC SERVICE ETHICS IN THE OFFICE OF THE REGIONAL DEVELOPMENT PLANNING AGENCY OF NORTH SULAWESI PROVINCE - Pangkey, Itje; H. Mamonto, Fitri; Timbuleng, Mutiara (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
This research aims to determine Public Service Ethics at the Regional Development Planning Agency Office of North Sulawesi Province. This research was carried out at the Regional Development Planning Agency of North Sulawesi Province. The type of research used is qualitative research, with data collection techniques through observation, interviews and documentation. The data obtained was analyzed descriptively qualitatively. The number of informants was 6 people. Based on the research results, it shows that public service ethics from the aspects of equality of rights, justice, loyalty and responsibility have not worked well and optimally. This can be seen from 1) Equality of Rights (equality), this is based on Equality of Rights in serving incoming guests, employees still discriminate. 2) Justice, this is based on unfair treatment which of course can be detrimental, and is not in line with the fifth principle, namely social justice for all Indonesian people. 3) Loyalty, this is based on a lack of employee loyalty, where due to environmental influences that cause a sense of loyalty to fade, employees have not fully complied with applicable official regulations. 4) Responsibility (responsibility) this is based on the employee's responsibility in carrying out and adjusting his work which has not gone well. Efforts given in public service ethics include maintaining and paying more attention to service ethics so that they are more effective and efficient, providing equitable services regardless of race, ethnicity, religion, politics, etc., increasing loyalty to work, being more responsible for every task and responsibilities given. Penelitian ini bertujuan untuk mengetahui Etika Pelayanan Publik di Kantor Badan Perencanaan Pembangunan Daerah Provinsi Sulawesi Utara. Penelitian ini dilaksanakan di Badan Perencanaan Pembangunan Daerah Provinsi Sulawesi Utara. Jenis penelitian yang digunakan yaitu penelitian kualitatif, dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Data yang diperoleh dianalisis secara deskriptif kualitatif, Jumblah informan yaitu 6 orang. Berdasarkan hasil penelitian menunjukkan bahwa etika pelayanan publik dari aspek persamaan hak, keadilan, kesetiaan, tanggung jawab belum berjalan dengan baik dan maksimal. Hal ini dapat dilihat dari 1) Persamaan Hak (equality) hal ini didasarkan pada Persamaan Hak dalam melayani tamu yang datang pegawai masih membeda-bedakan. 2) Keadilan (justice) hal ini didasarkan pada adanya perlakuan yang tidak adil yang tentunya dapat merugikan, dan tidak selaras dengan sila kelima yaitu keadilan sosial bagi seluruh rakyat Indonesia. 3) Kesetiaan (loyality) hal ini didasarkan pada kurangnya kesetiaan pegawai dimana karna pengaruh lingkungan yang membuat pudarnya rasa kesetiaan, pegawai belum sepenuhnya menaati peraturan kedinasan yang berlaku. 4)Tanggung Jawab (responsibility) hal ini didasarkan pada tanggung jawab pegawai dalam melaksanakan dan menyesuaikan pekerjaannya belum berjalan dengan baik. Upaya-upaya yang diberikan dalam etika pelayanan publik yaitu sebaiknya lebih mempertahankan dan memperhatikan etika pelayanan agar lebih efektif dan efisien, memberika pelayanan yang merata tanpa memandang ras, suku, agama, politik dll, meningkatkan kesetiaan terhadap pekerjaan, lebih bertanggung jawab terhadap setap tugas dan tanggung jawab yang diberikan.